“Semua Aku Dirayakan” in the Lyrics of Nadin Amizah’s Song - Tri Yanti Monika; Fahrul Rozi; Siti Khumayah; Aghnia Dian Lestari (Athena: Journal of Social, Culture and Society, 2025)
Music has a significant role as a universal communication tool that is able to express feelings, ideas, emotions and reflections to its listeners. The song "Semua Aku Dirayakan" by Nadin Amizah is not only a means of entertainment but also offers a deep meaning related to introspection about self-acceptance, gratitude, and life's journey through deep metaphors. This research uses a descriptive qualitative method with Ferdinand De Saussure's semiotic approach, which focuses on the relationship between signifiers and signifieds to help us understand how signs work to form, change and communicate meaning in certain contexts. Data was collected from fanbase and general listener interviews as well as lyric analysis. This research aims to analyze the meaning of the lyrics of the song "Semua Aku Dirayakan" to reveal the message contained and connected to the listener's interpretation. The results of this research show that the song "Semua Aku Dirayakan" can be a universal reflection medium with a deep meaning about self-acceptance and respect for every phase of life. This research provides theoretical contributions to the study of semiotics and practical benefits for listeners in understanding the meaning of song lyrics more deeply.